Implementation of Independent Learning in Independent Campus by Distance Learning at Private Universities in Bogor During the Covid 19 Pandemic - Arifien, Yunus; Susdiyanti, Tun; Maslahat, Mamay (Advances in Social Sciences Research Journal, 2022)
The Covid-19 outbreak has hit the world of higher education, forcing all universities in Bogor to implement a distance learning system. Distance learning means that there is a significant change from face-to-face conventional learning to distance learning from home. However, during this pandemic it is still rare for research to focus on distance learning on student satisfaction, the application of independent learning in independent campuses and the competence of graduates in private universities. This study aims to determine the implementation of independent learning on an independent campus by distance learning at private universities in Bogor during the covid 19 pandemic. The research method used is descriptive and different test. Data analysis includes reduction, presentation, and drawing conclusions. The results of the study can be concluded that (1) distance learning at universities has been carried out well during the covid 19 pandemic with the satisfaction level of PUAS students, (2) in the application of independent learning on an independent campus, subjects with calculations such as statistics are better with conventional learning methods instead of e-learning, it is a subject without a count, such as the environment and Pancasila, on the other hand. Likewise, for courses taken outside the study program, students can take part and get better grades, and (3) the competence of graduates from private universities through distance learning during the COVID-19 pandemic is good and can work and adapt in their place of work.